Implementation of Problem-Based Learning (PBL) in Islamic Religious Education (PAI) at Higher Education Institutions to Enhance Students' Moderate Attitudes - Firdaus, Muhammad Aditya Firdaus; Supiana Supiana; Uus Ruswandi; Mohamad Erihadiana; Opik Abdurrahman Taufik (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
This study is motivated by the issue of low levels of moderate attitudes among university students. The aim of this research is to determine the implementation of the Problem-Based Learning (PBL) Model in religious education at higher education institutions to enhance students' moderate attitudes. The research employs a Mixed Methods Research approach with a sequential explanatory design. The sample consists of 70 management students at Universitas Islam Nusantara. Data collection techniques include questionnaires, interviews, observations, and documentation studies. Quantitative data analysis employs simple regression analysis, while qualitative data analysis uses data reduction, data presentation, and conclusion drawing or verification. Based on the results, it can be concluded that the implementation of the PBL model in religious education significantly influences the enhancement of students' moderate attitudes. This is evidenced by a significance value of 0.001, which is less than the probability value of 0.05, and a coefficient of determination (R Square) of 0.234. This indicates that the contribution of the independent variable (PBL model in religious education) to the dependent variable (students' moderate attitudes) is 23.40%.